Venezuelan Equine Encephalitis and 2 Human Deaths, Peru - Vilcarromero, Stalin (Centers for Disease Control and Prevention, 2010)
Studies have suggested that enzootic strains of Venezuelan equine encephalitis (VEE) subtype ID in the Amazon region, Peru, may be less pathogenic to humans than are epizootic variants. Deaths of 2 persons with evidence of acute VEE virus infection indicate that fatal VEEV infection in Peru is likely. Cases may remain underreported.